Sourcing Prehistoric Ceramics at Chodistaas Pueblo, Arizona The Circulation of People and Pots in the Grasshopper Region (University of Arizona Press, 2022)
For decades archaeologists have used pottery to reconstruct the lifeways of ancient populations. It has become increasingly evident, however, that to make inferences about prehistoric economic, social, and political activities through the patterning of ceramic variation, it is necessary to determine the location where the vessels were made. Through detailed analysis of manufacturing technology and design styles as well as the use of modern analytical techniques such as neutron activation analysis, Zedeño here demonstrates a broadly applicable methodology for identifying local and nonlocal ceramics.